RETRACTED: Efficiency Measurement and Spatial Spillover Effect of Green Agricultural Development in China - Xu, Pei; Jin, Zehu; Ye, Xixi; Wang, Chen (Frontiers in Environmental Science, 2022)
Green agriculture is a mainstream focus for the sustainable development of agriculture. Based on the Chinese provincial agriculture panel data from 2010 to 2019, in this study, we adopted the slacks-based measure (SBM) super efficiency model, Sales Force Automation (SFA) model, and global Malmquist-Luenberger (GML) production index to measure the green development efficiency of agriculture. Meanwhile, Moran’s I and spatial econometric model were applied to analyze various factors influencing green agricultural development and spatial spillover effect. The threshold model was used to describe the relationship between the development scale of green agriculture and economic development. The results show that (1) Chinese green agricultural development efficiency is on a rising trend, and the measured effects of environmental factors and random disturbances on the efficient development of Chinese green agriculture were higher than those in reality. (2) The analysis of spatial effect of green agricultural development showed a direct positive effect from agricultural mechanization, science and technology innovation, industrial agglomeration, income level, and environmental rule and a direct negative effect from agricultural yield structure, farmland pollution, and agricultural disasters. Furthermore, industrial structure optimization and environmental rule evoke a demonstration effect, and technical innovation, income level, and agricultural industrial agglomeration triggered a siphonic effect. (3) The threshold model that was used to analyze the threshold value of the green agricultural development scale can be used to realize sustainable development of agriculture and economy.